Do isolamento à integração desgovernada da Amazônia: a “febre do ouro” e o “outro estado dentro do Estado” no caminho da rodovia Interoceânica por Madre de Dios - Prado Filho, Carlos Roberto Staine (2018)
The beginning of the current “gold fever” in the Madre de Dios region, in the South of the peruvian Amazon, is chronologically related with two factors: a) the implementation of the interoceanic highway e; b) the gold price record valorization in the world market. Within this horizon of approximately one decade, between the year 2005 until this moment, from a governance perspective the thesis points out that with insurgence of the “gold fever” the Madre de Dios region were transformed from an “isolated” region to a region that now experiences a generalized context of “ungoverned integration”. Having as a start point this chronological relation, it’s proposed a theoretical rereading from a Marxian perspective to frame such “gold fever” in the discussion about capital focused in concepts such as “primitive accumulation” and the process of “space annihilation for time”. Through the analysis about the supposedly innovator character that motivated the realization of the interoceanic highway as a project of the initiative known as Regional Integration of South America Infrastructure (IIRSA) and also through data collection of such project, the thesis aims to confront the positive expectations deposited in the highway by its promoters as a “integration and development” project. To confirm this contraposition, it’s presented the “disgovernance” scenario defined by the unsuccessful attempts of the State to control the territorial expansion of the illegal/informal gold mining along the interoceanic highway. It is also analyzed the predominant influence of such expansion on the socioeconomic and political dynamics in the local society and its relations with the evolution of the power of control by organized crime in the illegal gold mines in the middle of the Amazon forest